Seventh Five Year Plan (1985-90) and Annual Plan (1985-86) Government of Madhya Pradesh - Planning Commission (Planning Commission, 1985)
Sericulture is a cottage industry. With an agricultural base, industrial superstructure and an essentially labour intensive set up, sericulture is an effective tool for generating gain full employment to the retarded sectors of the community. Presently, it provides whole time employment 40 lacs persons in the rural areas of the country, of whom more than 30 per cent comprise of persons belonging to the retarded sections of society such as scheduled castes and scheduled tribes.
Directorate of Sericulture, (Rural Development Department), Government of Madhya Pradesh